Über die Struktur der Menge der verallgemeinerten Perioden - Naftalewitsch, A. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Нафталевич. О строении множества обобщенных периодовA. Naftalevičius. Apibendrintų periodų struktūra